The Early Paleozoic sedimentary record in northeastern Brazil: Unravelling the sedimentary provenance and evolution of fluvial systems after the Western Gondwana assembly - Cerri, Rodrigo I. [UNESP]; Warren, Lucas V. [UNESP]; Luvizotto, George L. [UNESP]; Spencer, Christopher J.; Assine, Mario L. [UNESP] (Elsevier, 2024)
The sedimentary units of the geographically isolated basins of NE Brazil are historically interpreted as coeval and part of the same depositional system that was ultimately responsible to the deposition of the first sedimentary sequence of the intracratonic Parnaíba Basin. We present the first integrated detrital zircon U-Pb age dataset from the Early Paleozoic basins of NE Brazil, providing new insights into the depositional evolution and erosional history after Western Gondwana assembly. The lowermost sedimentary units (Ipu, Cariri, and Tacaratu formations) of eleven NE Brazil sedimentary basins (Parnaíba, Araripe, Tucano-Jatobá, Lavras da Mangabeira, Fátima, São José do Belmonte, and Mirandiba) were analyzed by a multi-proxy approach aiming to propose new insights on the paleogeographic reconstruction and stratigraphic correlations. Sedimentary provenance data, together with paleocurrents measurements consistently towards NNW-NW, suggests that the primary source for all the Early Paleozoic sedimentary units of NE Brazil were elevated orogenic areas related to the Brasiliano Orogeny to the south of Borborema Province (e.g., Riacho do Ponta, Rio Preto, and Sergipano belts). Based on detrital zircon U-Pb ages, we position the beginning of sedimentation of these basins in the Ordovician. The U-Pb age spectra for all analyzed sedimentary successions are remarkably similar. The analysis of KDE plots, CA-DA gap curves, and (dis)similarity tests, reinforced the correlation and contemporaneity of all the Ordovician sedimentary successions of NE Brazil. The conceived paleogeography model points to deposition of all the analyzed successions in a ramp, slightly tilted towards NW, where continental-scale fluvial system drained Neoproterozoic orogenic areas (i.e., Brasiliano Orogeny) dispersing huge volumes of sediments towards Borborema Province interior.
Keywords: Early Paleozoic basins; Multi-proxy sediment provenance; Northeastern Brazil; U-Pb geochronology; Western Gondwana